Edukasi Seksual & Konseling Remaja untuk Pencegahan Pernikahan Dini di Klinik Bumi Sehat Desa Batu Mekar Kabupaten Lombok Barat - Isviyanti, Isviyanti; Triandini, I Gusti Agung Ayu Hari; Hairani, Hairani; Gumangsari, Ni Made Gita; Hidayati, Diana; Kandisa, Amelia; Mayasari, Astri; Gustiya, Sherly Dwi; Astuti, Ni Luh Budi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to provide sexual education and prevent early marriage to teenagers using a holistic psychological counseling and parenting approach, from a legal, social, and midwifery perspective. The method of implementing this service used counseling and mentoring on sexual and reproductive health education using a question-and-answer design. The targets of this activity were teenagers from Batu Mekar Village, West Lombok Regency who were still of school age using a questionnaire instrument which was then statistically analyzed using the t test. The results of this service showed that teenagers were aware of the impact of early marriage and understood anemia, and sexual reproductive health about the incidence of early marriage and stunting. By implementing this community service program, a youth posyandu/youth class was successfully established at the Bumi Sehat Clinic. This is useful in providing a forum for teenagers to discuss and consult regarding sexual, physical, and mental reproductive health issues as well as positive activities to prevent early marriage.